Genetic variation in domesticated cattle and wild aurochsen using ancient and modern data - Edwards, Ceiridwen Jane (Trinity College (Dublin, Ireland). Department of Genetics, 2003)
A total of 101 Bos taurus teeth and bones aged between 1,000 to 9,000 years old, and 45 B. primigenius primigenius bones aged between 3,720 to 12,380 years old, were assessed for the presence of verifiable mitochondrial sequences. It was possible to reproducibly amplify and sequence mitochondrial control region DNA extracted from twelve of the cattle and 24 of the aurochs samples. The sequences obtained from cattle were either identical, or closely related, to the reference sequence for modem cattle, highlighting the proximity of the ancient DNA cattle sequences to modem Near Eastern, European and African B. taurus, as well as regional continuity through time. As those samples taken from more arid areas gave considerably lower numbers of reproducible amplification, this analysis leads to the conclusion that remains from this type of excavation are less promising for archaeological genetics. Seven of the 24 aurochs control region sequences generated (29.2%) exhibited taurine-like haplotypes. Although this may be due to greater diversity of aurochsen prior to the last glaciation, which encompassed both the B. p. primigenius sampled here and the taurine haplotypes captured by domestication, it is more plausible that cross-breeding was occurring between early domestic cows and wild aurochs bulls. No clear divisions between those individuals with taurine-like or aurochs-like D-loop haplotypes were found when a region of the cytochrome b gene was sequenced in a subset of 19 aurochs. Comparisons between the 19 aurochs-like control region sequences and published extant data from Near Eastern B. taurus seem to suggest that the star-like patterns seen around the four main taurine haplotypes, previously explained as domestication-induced population expansion, may be due in part to capture of a greater diversity of extinct B. p. primigenius haplotypes at the domestication event.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin